2011
DOI: 10.5807/kjohn.2011.20.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Verbal Abuse, Emotional Response, and Ways to Deal with Verbal Abuse against Nurses in Hospital

Abstract: This study tries to identify experience of verbal abuse, emotional response, and ways to deal with verbal abuse against nurses in hospitals. Methods: This study was a descriptive research and conducted from April to July 2011. One hundred and seventeen nurses with over one-year experience in general wards were selected and evaluated. The data were analyzed using descriptive analysis, independent t-tests, and one-way ANOVA. Results: The nurses' experience rate of verbal abuse during the entire period of work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
0
4
0
2
Order By: Relevance
“…The perpetrators of verbal abuse were more often patients’ relatives than patients. This is presumably because, in the ED, patients’ relatives generally engage in open contact with the medical staff on behalf of the patient because of patients’ poor condition (Cho et al., ; Han et al., ). Furthermore, the unique characteristics of nursing work—in particular the need to constantly interact with patients and their families—mean that nurses are frequently exposed to conflict and tension, which in turn leads to an ever‐present risk of violence (Kim & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perpetrators of verbal abuse were more often patients’ relatives than patients. This is presumably because, in the ED, patients’ relatives generally engage in open contact with the medical staff on behalf of the patient because of patients’ poor condition (Cho et al., ; Han et al., ). Furthermore, the unique characteristics of nursing work—in particular the need to constantly interact with patients and their families—mean that nurses are frequently exposed to conflict and tension, which in turn leads to an ever‐present risk of violence (Kim & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…The perpetrators of violence towards emergency nurses are primarily patients. However, patients’ relatives are also a common source, as many relatives who visit the ED with patients must make contact with medical personnel on patients’ behalf, given that patients might be in too critical a condition to interact themselves (Cho et al., ; Han et al., ; Pich, Hazelton, Sundin, & Kable, ).…”
Section: Introductionmentioning
confidence: 99%
“…Postviolence management is uncommon, and participants' responses were passive in that they tolerated, avoided or adapted to the violence, and little is known about the methods and procedures applied for violence management. However, there are professional and systematic means such as access to professional procedures and personnel for handling violence, close networking with police and rapid access to professional and legal avenues to support coping or management . Nurses' satisfaction in the ways violence is handled is reported to be increasing .…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers are generally required in their profession to constantly communicate with doctors, patients, and guardians, and verbal violence may occur during this process. Studies on healthcare workers' experiences of verbal violence have reported that more than 90% of nurses have experienced verbal violence from patients, doctors, and/or colleagues 7,8) . Moreover, 96.4%…”
Section: Introductionmentioning
confidence: 99%